Inheritance Law in Indonesia: Challenges, Solutions, and the Role of Culture and Religion - Aliyah, Nelud Darajaatul; Evendi, Wakid (Bulletin of Science, Technology and Society, 2023)
The law of inheritance, known as faraid or mawaris in Islamic law, is a rule governing the transfer of ownership of the heir's property to the heir after the testator's death. In Indonesia, the inheritance law system is related to kinship and various cultures and religions influence its understanding and implementation. Conflicts often arise due to the variety of settlement systems, including Islamic law, customary, and civil law. This article highlights the need for a better understanding of inheritance law at all levels of society to reduce conflict and proposes solutions to improve understanding of inheritance in Indonesia's diverse context. The research method uses a qualitative-descriptive approach with data from various literature sources, including law, research, journals, and interviews with legal experts and scholars. This study aims to explore aspects of inheritance law in Indonesia, including cultural and religious implications as well as potential conflicts that can arise. Proposed measures to address inheritance law issues in Indonesia involve legal reform, education, promotion of gender equality, legal aid, dispute mediation, legal oversight, cross-sector collaboration, and accurate data collection. Just legal change and better understanding will help achieve fairness in inheritance sharing and promote harmony in Indonesia's diverse society. In conclusion, a good understanding of inheritance law, legal reform, education, and cross-sector cooperation are essential to overcome inheritance law problems in Indonesia (Basyir, 2001). This joint effort will have a positive impact on justice, gender equality, and the well-being of the Indonesian people.